Online gaming and peer social interactions: implications of defense of the ancients 2 (DOTA 2) and league of legends (LOL) to gamers studying at Pamantasan ng Lungsod ng Maynila - Arianne Uy. 4 0 16; 5 (2018)
u
Undergraduate Thesis: (B.S. Psychology) - Pamantasan ng Lungsod ng Maynila, 2018.
Keywords: 2 -- 0; 6; 20; 20; 2